Massive lipoma of the posterior neck - Virk, Jagdeep Singh (BMJ Case Rep, 2016)
Giant lipomas are a rare, benign cause of painless neck mass. We describe the case of a 63-year-old man with a giant lipoma of the left posterior neck, which presented with intermittent upper limb paraesthesia. Surgical excision confirmed the diagnosis of spindle-cell lipoma and resulted in complete resolution of neurological symptoms.